HUBUNGAN GURU DAN MURID MENURUT HADIS - Mulyadi Hermanto Nst (Universitas Muhammadiyah Tapanuli Selatan, 2018)
Abstraction There is an academic concern, if seeing something only from the perspective of the Hadith will castrate the viewpoint of the Qur'an. However, the reality that happens, instead of showing the viewpoint of the Qur'an, turns out to be 'forgetting' the Hadith. This paper will try to see the teacher-student relationship in a hadith perspective while remaining based on the world view of the Qur'an. That is, the worldview of the Qur'an about education is a foothold in the study of teacher-student relations in the hadith perspective.This study will first explain the theoretical perspectives of education about student teacher relations, in addition to tracing the traditions related to the topic of study, which at the same time make explanations and analyzes by determining the concept of teacher-student relations. At the end, the closing remarks will be made as a conclusion of the study. Keywords: Relationships, teachers, students, and hadith.